2007
DOI: 10.1111/j.1572-0241.2007.01537.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of CT Enteroclysis With Surgical Pathology in Crohn's Disease

Abstract: CTE may reliably differentiate between inflammatory and fibrostenotic lesions and may have an important role in the management of CD. Specific CTE variables correlate with each of these phenotypes and deserve further investigations in prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
144
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(159 citation statements)
references
References 32 publications
7
144
0
1
Order By: Relevance
“…The regression of inflammatory activity of CD at the strictureplasty site has been well documented by radiological, ultrasonographic, endoscopic or histological investigations [27][28][29][30][31] . During a reoperation, the surgeon can ap-…”
Section: Discussionmentioning
confidence: 99%
“…The regression of inflammatory activity of CD at the strictureplasty site has been well documented by radiological, ultrasonographic, endoscopic or histological investigations [27][28][29][30][31] . During a reoperation, the surgeon can ap-…”
Section: Discussionmentioning
confidence: 99%
“…On CT enteroclysis, active inflammation is suggested by mural and wall enhancement, mural stratification, lymphadenopathy, engorgement of vessels, and wall thickness; fibrostenotic strictures, however, are associated with nonenhancing wall thickening, proximal dilation, and luminal stenosis (6). We did not apply semiquantitative or qualitative criteria for reading the intravenous contrast-enhanced CT scans as done in other studies (6)(7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…Noninvasive anatomic and functional imaging modalities, including CT enteroclysis (6)(7)(8)(9), CT enterography, ultrasound, magnetic resonance enterography, and radiolabeled white blood cell and granulocyte scintigraphy (10)(11)(12)(13)(14)(15)(16)(17)(18)(19), have shown some ability to measure the extent and severity of active inflammation in CD. Neither these techniques nor endoscopy allows complete assessment of transmural inflammation or extraluminal complications of CD.…”
mentioning
confidence: 99%
“…Moreover, in all probability, the fact that the operative specimens were ''opened'' for pathologic assessment erroneously reduced the number of reference diagnoses of stricture. In the same study [55], CT enterography displayed 77 % sensitivity and 86 % specificity in the detection of fistulas and somewhat greater accuracy in the identification of intra-abdominal abscesses (sensitivity 86 %, specificity 87 %). The recent systematic review by Panes et al [46] looked at the results of several studies and found that CT enterography had an overall sensitivity of 70 % and specificity of 97 % in the detection of fistulas.…”
Section: Computed Tomographymentioning
confidence: 72%
“…The systematic review conducted by Panes et al [46] looked at the performance of CT enterography in identifying areas of stenosis in five studies [50][51][52][53][54] and found an overall sensitivity and specificity of 89 and 99 %, respectively. This method was also assessed in an interesting study by Chiorean et al [55]: compared with intraoperative findings, CT enterography exhibited 92 % sensitivity with a specificity of only 39 %. The relative nonspecificity of the examination was probably related to the fact that data in this retrospective nature were collected from surgeons' reports.…”
Section: Computed Tomographymentioning
confidence: 99%